Pelatihan Pembuatan Media Akuaponik bagi Warga Desa Bulu Kabupaten Batang - Prayogi, Arditya; C. Kurniawan, Pratomo; A. Tabi'in; Arisandi (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This community service activity is carried out with the main background so that the people of Bulu village, Batang district, can maximize the land where they live, especially with aquaponic-based agricultural activities. Thus, this service activity aims to increase knowledge and skills in making aquaponic media and being able to carry out aquaponic farming. The service method is carried out by providing training and outreach in collaboration with the Bulu village PKK team. The target objects were housewives in Bulu village. In general, the activity went well where the participation and enthusiasm of the participants who took part in this activity was very good as seen from the many questions asked so that the discussion could run actively. The impact of this training activity is that it can increase participants' knowledge and skills in making aquaponic media and using it in aquaponic farming so that it can provide more profitable harvest results.